2008
DOI: 10.1007/s10549-008-0128-9
|View full text |Cite
|
Sign up to set email alerts
|

Response to neoadjuvant therapy with cisplatin in BRCA1-positive breast cancer patients

Abstract: Background Ten patients with breast cancer and a breast cancer susceptibility gene 1 (BRCA1) mutation, who presented with stages I to III breast cancer between December 2006 and 2007, were treated with four cycles of neoadjuvant cisplatin, followed by mastectomy and conventional chemotherapy. Methods The excised breast tissue and lymph nodes were examined for the presence of residual disease. Results Pathologic complete response was observed in nine patients (90%). Conclusions Platinum-based chemotherapy appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
180
0
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 303 publications
(191 citation statements)
references
References 18 publications
3
180
0
8
Order By: Relevance
“…In contrast, BRCA1 expression levels had a wide range in MBC, which may provide an opportunity for its use as a predictive marker for platinum efficacy [24]. However, in contrast to RRM1 and ERCC1 where activating or inactivating mutations have not been described, assessment of the mutational status of BRCA1 may be crucial to the interpretation of the prognostic and predictive utility of its protein levels [25][26][27]. Interestingly, we found that BRCA1 levels were significantly correlated with both RRM1 and ERCC1 levels, similarly to what has been described in NSCLC [18].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, BRCA1 expression levels had a wide range in MBC, which may provide an opportunity for its use as a predictive marker for platinum efficacy [24]. However, in contrast to RRM1 and ERCC1 where activating or inactivating mutations have not been described, assessment of the mutational status of BRCA1 may be crucial to the interpretation of the prognostic and predictive utility of its protein levels [25][26][27]. Interestingly, we found that BRCA1 levels were significantly correlated with both RRM1 and ERCC1 levels, similarly to what has been described in NSCLC [18].…”
Section: Discussionmentioning
confidence: 99%
“…In a small clinical trial, cisplatin treatment for BRCA1-associated breast cancers appears to be promising (Byrski et al 2009). Similarly, BRCA1-and BRCA2-associated ovarian cancers were responsive to cisplatin or carboplantin treatment; however, resistance developed (Cass et al 2003).…”
Section: Targeting Aberrant Pathways In Breast Cancersmentioning
confidence: 99%
“…Cisplatin has been shown to have a high rate of clinical -pathological complete responses when used as neoadjuvant treatment of breast cancer arising in BRCA1-mutation carriers (Byrski et al, 2009;. Sporadic triple-negative breast cancers also had a significant rate of complete response to platinum therapy, suggesting that a subset of these cancers may be 'BRCA1-like' and have a similar defect in HR-mediated repair (Silver et al, 2010).…”
Section: Brca1 and Dna Repairmentioning
confidence: 99%